2018
DOI: 10.1089/neu.2017.5194
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Blood Transfusion and Coagulation Management in Traumatic Brain Injury at the Intensive Care Unit: A Survey in 66 Neurotrauma Centers Participating in the Collaborative European NeuroTrauma Effectiveness Research in Traumatic Brain Injury Study

Abstract: Our aim was to describe current approaches and to quantify variability between European intensive care units (ICUs) in patients with traumatic brain injury (TBI). Therefore, we conducted a provider profiling survey as part of the Collaborative European NeuroTrauma Effectiveness Research in Traumatic Brain Injury (CENTER-TBI) study. The ICU Questionnaire was sent to 68 centers from 20 countries across Europe and Israel. For this study, we used ICU questions focused on 1) hemoglobin target level (Hb-TL), 2) coag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…GOSE Glasgow Outcome Scale extended, ICP intracranial pressure, MOR median odds ratio combinations of these different factors. As for monitoring and management variations among centers, heterogeneity was not unexpected: previous studies [19][20][21] and surveys [22][23][24] found profound dissimilarities between centers in monitoring and treatment policies similar to our study.…”
Section: Between-center Differencessupporting
confidence: 84%
“…GOSE Glasgow Outcome Scale extended, ICP intracranial pressure, MOR median odds ratio combinations of these different factors. As for monitoring and management variations among centers, heterogeneity was not unexpected: previous studies [19][20][21] and surveys [22][23][24] found profound dissimilarities between centers in monitoring and treatment policies similar to our study.…”
Section: Between-center Differencessupporting
confidence: 84%
“…Patients with isolated TBI receive plasma transfusions primarily to revers trauma‐induced or medically induced coagulopathy. In a provider‐profiling survey that included 66 centers from 20 European countries, fresh frozen plasma was transfused to treat hemostatic abnormalities in 73% of patients with TBI . A small retrospective study found that plasma transfusion before hospital admission reduced the average international normalized ratio (INR) upon admission from 3.1 to 1.9 in patients with TBI on warfarin, but the clinical outcomes for these patients were not reported .…”
Section: Plasma Transfusionmentioning
confidence: 99%
“…In a provider-profiling survey that included 66 centers from 20 European countries, fresh frozen plasma was transfused to treat hemostatic abnormalities in 73% of patients with TBI. 56 A small retrospective study found that plasma transfusion before hospital admission reduced the average international normalized ratio (INR) upon admission from 3.1 to 1.9 in patients with TBI on warfarin, but the clinical outcomes for these patients were not reported. 57 The transfusion of fresh or lyophilized fresh frozen plasma (FFP) has been reported to reduce neurologic impairment and accelerate the recovery of Yorkshire swine subjected to TBI and controlled hemorrhagic shock as compared to those receiving normal saline.…”
Section: Plasma Transfusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Provider Profiles of participating centres were established to characterize structures and processes of care in preparation for comparative effectiveness research. [5][6][7][8][9][10] We here aim to describe the contemporary landscape of TBI in Europe, with a focus on the patient case-mix, care pathways, and outcome in the Core study, and to explore generalizability by comparison to the Registry.…”
Section: Introductionmentioning
confidence: 99%